The role of antioxidants and pro-oxidants in colon cancer - Stone, William L (Baishideng Publishing Group Co., Limited, 2014)
This review focuses on the roles antioxidants and pro-oxidants in colorectal cancer (CRC). Considerable evidence suggests that environmental factors play key roles in the incidence of sporadic CRC. If pro-oxidant factors play an etiological role in CRC it is reasonable to expect causal interconnections between the well-characterized risk factors for CRC, oxidative stress and genotoxicity. Cigarette smoking, a high dietary consumption of n-6 polyunsaturated fatty acids and alcohol intake are all associated with increased CRC risk. These risk factors are all pro-oxidant stressors and their connections to oxidative stress, the intestinal microbiome, intestinal microfold cells, cyclooxygenase-2 and CRC are detailed in this review. While a strong case can be made for pro-oxidant stressors in causing CRC, the role of food antioxidants in preventing CRC is less certain. It is clear that not every micronutrient with antioxidant activity can prevent CRC. It is plausible, however, that the optimal food antioxidants for preventing CRC have not yet been critically evaluated. Increasing evidence suggests that RRR-gamma-tocopherol (the primary dietary form of vitamin E) or other “non-alpha-tocopherol” forms of vitamin E (e.g., tocotrienols) might be effective. Aspirin is an antioxidant and its consumption is linked to a decreased risk of CRC.